Implementation of Technological Pedagogical and Content Knowledge (TPACK) in English Teaching and Learning (Case Study at SDIT Al Hasna Klaten in The 2024/2025 Academic Year) - Niken Palupi; Hersulastuti; Purwo Haryono (Qalam : Jurnal Ilmu Kependidikan, 2025)
This study aims to: Describe the implementation of TPACK in the English learning process for students of SDIT Al Hasna Klaten Describe the obstacles experienced by English subject teachers at SDIT Al Hasna Klaten students in implementing TPACK and describe the solutions to the obstacles experienced by English subject teachers at SDIT Al Hasna Klaten students in implementing TPACK; and 4. Elaborate the reasons for the solutions made in implementing TPACK by English subject teachers at SDIT Al Hasna Klaten students. This study uses a qualitative descriptive research method that aims to explain the problems that arise and describe data in the form of sentences according to the facts during the study in order to understand the phenomenon of the implementation of TPACK in English learning at SDIT AlHasna. The results of the study show that the Technological Pedagogical And Content Knowledge (TPACK) Indicator, namely the suitability between strategy and technology with the material taught by Al Hasna Klaten English Teachers, has combined three basic components, namely technological knowledge, pedagogical knowledge and content knowledge in learning carried out by English Teachers so that learning takes place smoothly, comfortably, focused and enjoyable. The obstacles faced by the implementation of TPACK in the English learning process for students of SDIT Al Hasna Klaten are generally non-existent and insignificant. If these types of obstacles occur, their nature is only to increase the capacity of existing facilities and always improve teacher competence, especially the latest technology, intensifying things that are lacking that are adjusted to developments in the world of education. The solution to overcome the obstacles faced by the implementation of TPACK in the English learning process for students of SDIT Al Hasna Klaten in principle has been adjusted to the types of obstacles or weaknesses of the existing and occurring problems. The reason for choosing problem solving in overcoming the obstacles faced from the implementation of TPACK in the English learning process for students of SDIT Al Hasna Klaten, is basically right because it has been adjusted to the abilities, situations and conditions that exist at SDIT Al Hasna Klaten. Support from related agencies, for example from the Department of Education and Culture, also needs to be optimized.